STRIVE FOR SUCCESS OF FOUR MAIN CHARACTERS IN RICK RIORDAN’S HEROES OF OLYMPUS: THE MARK OF ATHENA NOVEL - MAHFUSH, MUHAMMAD HAVIST (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: strive for final goal, strive for success, strive for power, novel.The discussion in this thesis is about four demigods who must reach the goal in their missions. Heroes of Olympus: The Mark of Athena Novel was written by Rick Riordan and was published in 2012. The focus of this thesis is to analyze the exertion and the characteristics of the four characters in achieving their goals. The theory of strive for final goal by Alfred Adler is used in this thesis. This theory describes human characteristics in achieving a goal. Strive for the final goal has two sub-theories. Strive for success for people who want to achieve goal for all humankind and strive for power in the contrary.The result of this study shows that the theory of strive for success dominates the characteristics of the four characters that the author analyzes. Annabeth is a character who seeks for peace which belongs to strive for success characteristic. This model of character prefers unity rather than a division. Leo has the characteristic of creative power. This characteristic often gives a brilliant idea. Percy has a characteristic of caring with others. Piper has the characteristic of willing to sacrifice. All these model of character are in Adler’s theory strive for success.The author has suggestions for further researchers who want to analyze Rick Riordan’s Heores of Olympus: The Mark of Athena novel. The author suggests using mythological theory to analyze this novel. Aspects of Greek mythology are much in this novel which is very interesting to be analyzed.